(3GdbGfhf GdOhdj GdNGU (B/s - (3GdaJdGhj, Sgjd MSjfs ((3GdbGgQI(B: s (3GdecJH GdeUQj dJhRjY GdeWHhYGJ(B, s, 2002)
(3HGdfX``````Q Edj Cf GdbGfhf GdOhdj GdNGU jfXe ehVhYGJ bGfhfjI eJYOOI , hgj GdLfSjI hGdehWf hGdeQcR GdbGfhfj ddCLGfH hJfGRY GdGNJUGU GdbVGFj h JfGRY GdbhGfjf , abO GNJda GdabgGA aj hVY JYQja LGeY eGfY ddbGfhf GdOhdj GdNGUJfGhd gPG GdcJGH GdaUd CdChd (B: (3GdeHGOiA GdYGeI ddbGfhf GdOhdj GdNGU GdaUd GdKGfj (B: (3GdLfSjI GdaUd GdKGdK (B: (3Gde````````hGWf GdaUd GdQGHY (B: (3eQcR GdCLGfH GdaUd NGeS (B: (3JfGRY GdbhGfjf GdaUd GdSGOS (B: (3GdGNJGU GdbVGA GdOhdj GdaUd GdSGHY (B: (3JfajP GdCMcGe h GdbQGQGJ GdCLfHjIs
(3HjHdjhZQGajG (B:(3U(B. 361s
Keywords: (3GdLfSjIs; (3bGfhf GdOhdj GdNGUs